AWAL RADIKALISME ISLAM: PENYEBAB KEMUNCULAN KHAWA - Ahmad Choirul Rofiq (AL-TAHRIR, 2014)
In Islamic history, the emergence of khawarij is considered to be the first seed of Islamic radicalism. Studies on this radical group cannot be separated from the period of early Islam when it emerged. As a political movement and school of theology, this group was shaped by the social and political constellations in its time.  This article traces the historical root of this early radical group in Islam. Historians argue that the birth of khawarij was caused by political cleavage and tension upon Caliph Ali ibn Talib and Muawiya ibn Sufyan friction. However, the embryo of khawarij was in fact discovered during the time of the Prophet represented by Dhu al-Khuwaysirah in the course of the post Hunayn War. Various factors spurred the rise of khawarij, ranging from geographical factor, fanaticism, Shiffin War to provocation from Abd Allah ibn Saba’. Khawarij developed as one major stream in Muslim theology and broke into several extreme and radical splinter groups. The development of khawarij covers three phases: religious thought, political movement and political power.Keywords: khawarij, developmental phase, opposition